The taxonomic identity of two neglected Sprengel names, Galinsoga megapotamica and G. uniflora (Asteraceae), with remarks upon Friedrich Sellow’s collections galore - Moraes, Pedro Luís Rodrigues De (Phytotaxa, 2020)
The names Galinsoga megapotamica and G. uniflora (Asteraceae) are investigated. Specimens from Kurt Sprengel’s private herbarium, currently at the Paris Herbarium (P), are designated as lectotypes. These names are currently recognized under Hymenoxys and Helenium, respectively. Galinsoga megapotamica is proposed as a new heterotypic synonym of Hymenoxys tweediei, having nomenclatural priority over the latter, therefore I here propose its nomenclatural transfer as Hymenoxys megapotamica comb. nov. (≡ G. megapotamica). Similarly, Galinsoga uniflora is proposed as a new heterotypic synonym of Actinea heterophylla and Helenium radiatum (≡ Cephalophora radiata). Although Actinea heterophylla has nomenclatural priority over both G. uniflora and C. radiata, the epithet heterophyllum is unavailable in Helenium due to H. heterophyllum published by Candolle. Since Galinsoga uniflora is the next earliest legitimate name at the same rank, its final epithet is to be used instead, under Art. 14.1 of the ICN, thus a new combination is proposed: Helenium uniflorum comb. nov. (≡ G. uniflora). Additionally, lectotypes for the names Conyza oblongifolia, Hymenoxys tweediei and Onoseris stricta are designated, and remarks about the provenance of Friedrich Sellow’s collections related to Sprengel’s names in Asteraceae are also provided.